ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY, PURCHASE INTENTION AND PRICE ON CUSTOMER SATISFACTION IN THE USE OF ONLINE OJEK - Bella Oktavia Maulina Simanjuntak; Maria Regina Manalu; Elina Tobing; Holfian Daulat Tambun Saribu; Rintan Br. Saragih (Jurnal Ekonomi, 2023)
This study aims to examine how much influence service quality, purchase intention and price have on customer satisfaction when using OK online. This research method uses the methoddescriptivewith a quantitative approach. The study used the SPSS version 2.5 application with 96 respondents. Services have a positive and significant effect on customer satisfaction for online motorcycle taxi users according to the results processed from the respondent's data. With a calculated t value of 2.222 and a relevant level of 0.029. The results of the research analysis of Buying Interest obtained a t-count value of 2.916 and a significant level of 0.004, which has a positive and significant effect on customer satisfaction for users of online motorcycle taxi transportation. The price variable from the t-count test is 5.637 and a relevant level of 0.001 has a positive and dominant effect on the dependent variable, namely customer satisfaction with online motorcycle taxi users on Jalan Ayahanda, Medan. service Quality, Purchase intention and price have a positive and significant effect on the dependent variable studied, namely customer satisfaction with online motorcycle taxi users, Jalan Ayahanda, Medan. According to the data studied, calculated and presented in this study.